2014
DOI: 10.1097/pcc.0000000000000271
|View full text |Cite
|
Sign up to set email alerts
|

Intrapulmonary Instillation of Perflurooctylbromide Improves Lung Growth, Alveolarization, and Lung Mechanics in a Fetal Rabbit Model of Diaphragmatic Hernia

Abstract: Fetal perfluorooctylbromide treatment improves lung growth, lung mechanics, and extracellular matrix remodeling in hypoplastic lungs, most probably due to transient pulmonary stretch, preserved fetal breathing movements, and its physical characteristics. Perfluorooctylbromide instillation is a promising approach for prenatal therapy of lung hypoplasia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…In pilot experiments, tracheal injection of BAY 41-2272 using doses up to 16 mg/kg body wt did not affect fetal survival, body weight, or organ weights (data not shown). Moreover, the safety of fibrin sealant has already been reported in rabbit fetuses (33,45). At term (31 days), living fetuses were delivered by cesarean section and weighed.…”
Section: Methodsmentioning
confidence: 92%
See 1 more Smart Citation
“…In pilot experiments, tracheal injection of BAY 41-2272 using doses up to 16 mg/kg body wt did not affect fetal survival, body weight, or organ weights (data not shown). Moreover, the safety of fibrin sealant has already been reported in rabbit fetuses (33,45). At term (31 days), living fetuses were delivered by cesarean section and weighed.…”
Section: Methodsmentioning
confidence: 92%
“…Anesthesia and general surgical procedures have been described elsewhere (65,66). The feasibility of tracheal injection of medication has already been shown in the fetal rabbit (17,33). Briefly, at 23 days of gestation (pseudoglandular stage of lung development), two ovarian-end fetuses per doe were subjected to the surgical creation of diaphragmatic hernia (DH) through a left thoracotomy (23).…”
Section: Methodsmentioning
confidence: 99%
“…Also there was improvement in pulmonary function tests, airway (RAC) or vascular morphometry (reduced vessel thickness) compared to controls. Recently, it was shown that IT perfluorocytylbromide (PFOB) also improved lung mechanics …”
Section: Resultsmentioning
confidence: 99%
“…Recently, it was shown that IT perfluorocytylbromide (PFOB) also improved lung mechanics. 34 In lambs, maternal PO tadalafil (phosphodiesterase inhibitor) improved fetal pulmonary blood flow but had no impact on LBWR (Table 4). 62 A second study in the lamb model delivered a single dose of KGF IT which had little impact on RAC or LBWR.…”
Section: Isolated Studiesmentioning
confidence: 99%
“…TLV use is motivated by evidence of a more homogenous lung recruitment ( Hirschl et al, 1994 ; Tooley et al, 1996 ) and its potential as an efficient technique to remove pulmonary aspiration debris ( Foust et al, 1996 ; Avoine et al, 2011 ). Moreover, PFCs have low surface tension, anti-inflammatory properties ( Thomassen et al, 1997 ; Rotta and Steinhorn, 1998 ; Khalighi et al, 2016 ) and have been shown to promote lung growth ( Nobuhara et al, 1998 ; Herber-Jonat et al, 2014 ). PFCs are known for their high solubilities for most gasses ( Riess, 2005 ) enabling them to be used for respiratory support.…”
Section: Introductionmentioning
confidence: 99%